Identifying low test-taking effort during low-stakes tests with the new Test-taking Effort Short Scale (TESS): development and psychometrics - Schüttpelz-Brauns, Katrin (BMC medical education, 2018)
Low-stakes tests are becoming increasingly important in international assessments of educational progress, and the validity of these results is essential especially as these results are often used for benchmarking. Test scores in these tests not only mirror students’ ability but also depend on their test-taking effort. One way to obtain more valid scores from participating samples is to identify test-takers with low test-taking effort and to exclude them from further analyses. Self-assessment is a convenient and quick way of measuring test-taking effort. We present the newly developed Test-taking Effort Short Scale (TESS), which comprises three items measuring attainment value/intrinsic value, utility value, and perceived benefits, respectively.
Gesehen am 29.09.2020